2000
DOI: 10.1034/j.1399-3089.2000.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of xenoreactive antibodies by protein‐A immunoadsorption: experience in 22 patients

Abstract: The presence of naturally occurring anti-Galalpha1-3Gal (antialphaGal) Ab in human serum is believed to be a major factor in the pathogenesis of hyperacute rejection of discordant organ xenografts such as the pig-to-human combination. Galalpha1-3Gal epitopes are expressed on pig tissues and the binding of anti-Galalpha1-3Gal leads to endothelial cell activation and complement-mediated hyperacute graft rejection. Several strategies have been suggested in donor animals or in the xenograft recipient to overcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Non‐specific extracorporeal immunoadsorption using protein‐A or antihuman immunoglobulin linked to a stationary phase such as Sepharose or silica are also well‐documented techniques used for the removal of ABH‐, HLA‐ and xenoantibodies 106 , 110 , 112 , 113 , 114 , 115 , 116 , 117 . However, all types of antibodies are removed by these techniques, including those acting as the first line of defence against infections, including viruses 25 .…”
Section: Strategies To Eliminate/neutralize Preformed Anti‐carbohydramentioning
confidence: 99%
“…Non‐specific extracorporeal immunoadsorption using protein‐A or antihuman immunoglobulin linked to a stationary phase such as Sepharose or silica are also well‐documented techniques used for the removal of ABH‐, HLA‐ and xenoantibodies 106 , 110 , 112 , 113 , 114 , 115 , 116 , 117 . However, all types of antibodies are removed by these techniques, including those acting as the first line of defence against infections, including viruses 25 .…”
Section: Strategies To Eliminate/neutralize Preformed Anti‐carbohydramentioning
confidence: 99%
“…The induction of specific immune tolerance has been reported to be a feasible approach to treating organ rejection [21]. Galalpha1-3Gal epitopes were expressed in pig tissues and the binding of anti-Galalpha1-3Gal led to endothelial cell activation and complement-mediated hyperacute graft rejection [22]. Recently, galectin-1 was demonstrated to significantly attenuate allogeneic immune responses in murine LT models [5].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies to prevent hyperacute rejection have included efforts to inhibit anti‐gal antibodies with synthetic galactosyl inhibitors [23], and efforts to absorb the antibodies with columns [24,25]. Dalmasso and colleagues found that pig endothelium up‐regulates expression of CD59 after treatment with a gal‐binding lectin [26].…”
Section: Hyperacute Rejectionmentioning
confidence: 99%